Modified linear combination fitting for large-area two-dimensional chemical state mapping. (October 2020) - Tabuchi, Masao; Sakamoto, Ren; Takeda, Shingo; Konishi, Shunsuke; Suzuki, Toshimasa; Nagami, Tetsuo
Abstract: In order to reduce the XAFS/XANES measurement time for the wide area two- or three-dimensional chemical state mapping, modified linear combination fitting method have been developed. When the method is used, we can analyze the chemical states by measuring x-ray absorption coefficient at only several energy points. The detail of the method is precisely described. One of the important feature of the method is that the target spectrum is not required to be preliminarily normalized. Some of the two-dimensional maps obtained using the method have been shown as examples, where it is shown the distribution of the chemical state of the target element in samples have been clearly obtained by using the method. Highlights: Newly developed modified linear-combination-fitting method to analyze XANES spectra. Drastic reduction of measured energy points to realize chemical state wide maps. Clear demonstrations of the chemical state maps obtained by the new method.